Chemical assessment and antimicrobial activity of colored groundwaters. - Escuton, John Rey Rivera
This study was conducted to provide information on the quality of colored groundwater collected from Sta. Barbara, and Badiangan and to provide baseline information on the presence of the amount of heavy material.